Estudo da co-dopagem com Gd2O3 e CuO em soluções sólidas à base de céria - Silva, Thamyscira Herminio Santos da (2016)
Due to the increasing demand for new energy sources, solid oxide fuel cell has proven to be a good alternative, for these devices can support a large variety of fuels and applications. Solid solutions based on Cerium (CeO2) have been considered a promising material for electrolytes due to better ionic conductivities in comparison to yttrium stabilized zirconia. The main disadvantage of ceria-based electrolyte is the need for high sintering temperatures for complete densification. The solution to low sinterability of doped ceria is related to the addition of transition metal oxides, which has low melting point, such as CuO. Thus, this work is focused on the behavior of ceria solid solutions with CuO, co-doped with content of gadolinium (Gd2O3) in the 0-30 mol% range about the sinterability, microstructure and electrical properties. Gd-doped ceria (Ce0,99-xGdxCu0,01O2-δ (0 ≤ x ≤ 0,3)) was synthesized by the polymeric precursor method. Thermal analysis was used in powders heat-treated at 300 °C in order to determine the ideal calcinations temperature. The X-ray diffraction combined with Rietveld refinement was applied to the powders calcinated to determine their crystallographic features. Relative density measurements and microstructural analysis were performed sintered in the temperature range 950-1050 °C in air. Electrical properties were investigated by impedance spectroscopy. XRD results imply the effective formation of crystalline solid solutions with cubic fluorite structure by polymeric precursor method, as well as a decrease in crystalline size by increasing gadolinium content. The densification improves and the grain size decreases by gadolinium doping. Electrical conductivity increases by adding Gd reaching a maximum of 7.81 mS/cm at 600 °C for the sample with 15 mol% of this dopant.